Alignment of Financial Reporting of BUMDes Guwosari with Financial Accounting Standards - Handayani, Anik Puji; Windriyati, Fatimah Isna (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2023)
Government Regulation (PP) Number 11 of 2021 strengthens the existence of BUMDES as a legal entity. BUMDes financial reports are a form of responsibility for the productive implementation of BUMDes so that the presentation of financial reports must be in accordance with financial accounting standards. The approach for preparing BUMDes financial reports that meets the requirements is SAK ETAP. Guwosari BUMDes is in Guwosari Village, Pajangan subdistrict, Bantul Regency, DIY. The purpose of this research is to find out whether the financial reports of BUMDes Guwosari are in accordance with applicable standards and to find out the obstacles faced in implementing reports that comply with accounting standards. This research was carried out using the observation method and the fixed overview comparison method. The results of this research show that the elements of recording financial reports have increased every year, but are not yet fully in accordance with SAK ETAP. Human resources in the financial sector are the main obstacle for BUMDes Guwosari.